Adaptasi Morfologi, Keanekaragaman dan Distribusi Paku Epifit (Pteridophyta) di Bukit Cogong, Taman Nasional Kerinci Seblat - Reny Riastuti; Yunita Wardianti; Sepriyaningsih; Mareta Widiya; Rahmi (Jurnal Biosilampari : Jurnal Biologi, 2025)
Epiphytic ferns (Pteridophyta) are vital components of tropical forest ecosystems due to their role in maintaining microclimate humidity, supporting nutrient cycles, and providing habitat for small fauna. This study aims to identify epiphytic fern species and analyze their morphological adaptations and spatial distribution patterns in Bukit Cogong, a part of the Kerinci Seblat National Park (TNKS). The research employed a descriptive-explorative method using both quantitative and qualitative approaches. Six purposively selected plots measuring 20×20 meters were established across various microhabitat conditions. Data were collected through species inventory, morphological observations, and measurement of environmental parameters. Results revealed seven species of epiphytic ferns, including Pyrrosia piloselloides, Asplenium nidus, and Davallia trichomanoides. The Shannon-Wiener diversity index ranged from 1.67 to 1.86, indicating moderate to high diversity levels. Each species exhibited distinct morphological adaptations to the epiphytic lifestyle, such as frond shape, rhizome structure, and trichome presence. Species tended to exhibit a clustered spatial distribution, influenced by microclimatic heterogeneity and host tree characteristics. These findings contribute to the understanding of adaptive strategies in epiphytic ferns and support conservation efforts for species and habitats within TNKS.